Analyse paléoécologique des formations récifales du golfe de Skoura (bordure méridionale du sillon Sud rifain; SE de Fés; Maroc) implications paléogéographiques: communications Atlantique - Méditerranée au Miocène Terminal - Lachkhem, H. (2010)
The reef levels of the gulf of skoura belong to the reef formation of the Upper Miocene of the South-Rifan straits. A detailed analysis of the vertical distribution of various forms of colonies has led to the establishment of precise coral morphologies zonation. This palaeoecological approach leads us to distinguish between two environments in the Skoura gulf, probably corresponding to two reef episodes. The palaeogeographical implications (relationships between the Atlantic ocean and the Mediterranean sea) will be pointed out.